Progress of the Architectural Competition: Learning Center, the Lausanne Example - Rittmeyer, Mirjana; Aymonin, David; Joye, Nicolas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
Point of entry to the Ecole Polytechnique Fédérale de Lausanne (EPFL), the Learning Center will be a place to learn, to obtain information, and to live. Replacing and improving the old main library, this new building will gradually assimilate all EPFL department libraries collections and services, as they are integrated into a global information system. Conceived as the place for those who are learning, mainly students, who have no personal working area on the campus, it is designed to adapt itself to the ‘seasons’ of academic life throughout the year (flexibility and modularity of rooms, extended opening hours during exam periods). It will take into account group working habits (silence vs. noise), changes in the rhythm of student life (meals, working alone, discussions, etc.), and other environmental factors. Of course the needs of EPFL staff and alumni, local industry and citizens have also been carefully considered in the design. By offering a multitude of community functions, such as a bookshop, cafeteria and restaurant services, and rooms for relaxation and discussion, the Learning Center will link the campus to the city. Areas devoted to exhibition and debate will also be included, enforcing its role as an interactive science showcase, in particular for those technologies related to the research and teaching of the EPFL. The presentation described the process and steps towards the actual realisation of such a vital public space: from the programme definition to the collaboration with the bureau of architects (SAANA, Tokyo) who won the project competition, the speakers showed what are the challenges and lessons already taken when working on this major piece of architecture, indeed the heart of the transformation of the technical school build in the 1970s into a real 2000s campus.